1723. MK-3866, a metallo-β-lactamase inhibitor, is not subject to efflux in Pseudomonas aeruginosa. (15th December 2022) - Young, Katherine; Mirza, Asra; Balibar, Carl; Dong, Shuzhi; Bennett, Frank; Jiang, Jinlong; Tang, Haiqun; Tudge, Claire; Scott, Jack; Yang, Dexi; Pasternak, Alexander
Abstract: Background: Metallo-beta (β)-lactamases (MBLs) are in the class B group of β-lactamases due to zinc ions in the active site that are required for enzymatic activity. MK-3866 is a small molecule MBL inhibitor (MBLi) that restores antibacterial activity against resistant MBL-expressing gram-negative bacteria. Efflux is an important mechanism of antibiotic resistance in Pseudomonas aeruginosa (Pa). Imipenem (IMI) is not subject to efflux and neither is relebactam (REL), a β-lactamase inhibitor (BLi) of class A and C β-lactamases that is approved in combination with IMI/cilastatin. An efflux assay was devised to characterize MBLis for potentiation of IMI or cefepime (FEP) in isogenic strain pairs of efflux wild-type and multiply efflux deleted (MED) strains of Pa. Our objective was to determine if MK-3866 and related analogs are subject to efflux in Pa. Methods: Bacterial isolates were engineered to demonstrate the ability of MBLis to be effluxed by introducing IMI metallo-β-lactamase-1 (IMP-1) (by electroporation) or Verona integron-encoded metallo-β-lactamases (VIM-1, VIM-2) (utilizing the cloning vector pFlp2) into isogenic MED and wild-type (WT) Pa isolates. Susceptibility testing was performed with IMI or FEP at a fixed concentration equal to the Pa Clinical and Laboratory Standards Institute susceptibility breakpoint for each and including a fixed 4 µg/mL of REL to inhibit class A or C enzymes, referred to as the SLICE assay. The concentration of MK-3866 and analogues required to restore susceptibility to either antibiotic in WT and MED strains was assessed. Results: MICs to the combination of MK-3866/REL/IMI or MK-3866/REL/FEP vary by ≤4-fold between the WT and MED strain of each isogenic strain pair (Table 1). In contrast, large differential MIC values (efflux ratios) can be seen for the MK-3866 analogues A and B, with more moderate efflux ratios observed for other analogues. The exact efflux ratio depended on the MBL studied and the antibiotic partner. Conclusion: MK-3866 showed a low potential for efflux whether IMP-1, VIM-1, or VIM-2 was expressed, in contrast to analogues of MK-3866 which exhibited differentials from nominal to extreme (≥ 128-fold) between efflux WT versus MED isolates. Disclosures: Katherine Young, M.S., Merck & Co., Inc.: Stocks/Bonds Asra Mirza, MS, Merck & Co., Inc.: Stocks/Bonds Carl Balibar, PhD, Merck & Co., Inc.: Stocks/Bonds Shuzhi Dong, PhD, Merck & Co., Inc.: Stocks/Bonds Frank Bennett, PhD, Merck & Co., Inc.: Stocks/Bonds Jinlong Jiang, PhD, Merck & Co., Inc.: Stocks/Bonds Haiqun Tang, PhD, Merck & Co., Inc.: Stocks/Bonds Claire Tudge, PhD, Merck & Co., Inc.: Stocks/Bonds Jack Scott, PhD, Merck & Co., Inc.: Stocks/Bonds Dexi Yang, PhD, Merck & Co., Inc.: Stocks/Bonds Alexander Pasternak, PhD, Merck & Co., Inc.: Stocks/Bonds.